The Roles of Nurses in Health Coaching to Improve Self-Care Management among People with Type 2 Diabetes Mellitus: A Scoping Review - M Syikir; Sjattar, Elly L; Kadar, Kusrini S; Najamuddin, Nur Isriani (Genius Journal, 2025)
Introduction: Type 2 diabetes mellitus (T2DM) is a global health concern requiring long-term self-care management. Health coaching has emerged as a behavioral intervention to support individuals with T2DM, yet the specific roles of nurses within this context remain underexplored. Objective: This scoping review aims to map existing literature regarding the roles of nurses in health coaching interventions designed to enhance self-care management among individuals with T2DM. Method: The review followed the Joanna Briggs Institute (JBI) methodology for scoping reviews. A systematic search was conducted across databases including PubMed, ScienceDirect, Wiley Online, and ProQuest, targeting peer-reviewed studies published between 2009 and 2019. Articles were selected based on predefined inclusion criteria and underwent thematic analysis to identify recurring roles of nurses. Results: Thirteen studies met the inclusion criteria. Four primary nursing roles emerged in health coaching for T2DM patients: educator, supporter, advocate, and care coordinator. Nurses provided individualized and group education, emotional and informational support, facilitated communication with healthcare providers, and ensured continuity of care through coordination. Three models of care coordination were identified, with nurses acting as intermediaries, collaborators, or lead coaches. Conclusion: Nurses play multifaceted roles in health coaching to enhance self-care management in individuals with T2DM. Among the identified roles, the integration of educational and supportive functions showed the greatest impact on improving patient outcomes. These findings underscore the importance of integrating nurse-led health coaching into diabetes care strategies to empower patients and improve glycemic control.